Physicochemical and Sensory Quality of Meat in Commercial Native Chicken, Backyard Native Chicken, Commercial Broiler and Spent Layer Chicken: 10.5958/2581-6616.2020.00007.9 - kumar, Sathish; Kulkarni, V. V. (Journal of Meat Science, 2021)
A study was planned on the physicochemical and sensory quality of meat in commercial native chicken (CNC), backyard native chicken  (BNC), commercial broiler (CB) and spent layer chicken (SLC) on 12 birds of either sex in each class. Birds slaughtered by Jatka meth od and physico-chemical parameters (pH, Water Holding Capacity, Extract Release Volume, Muscle fibre diameter, sarcomere length,  collagen content, R-Value, shear force value and sensory score) were recorded in breast and leg meat, separately. Nuggets were prepared  to assess the sensory quality. Water Holding Capacity (WHC) was significantly higher (P
Keywords: Collagen content; Poultry meat; Physico chemical quality; Sensory quality